MTDH antisense oligonucleotides reshape the immunosuppressive tumor microenvironment to sensitize Hepatocellular Carcinoma to immune checkpoint blockade therapy. (10th August 2022) - Wan, Jing-Lei; Wang, Biao; Wu, Mei-Lan; Li, Jie; Gong, Ruo-Mu; Song, Li-Na; Zhang, Han-Shuo; Zhu, Gui-Qi; Chen, Shi-Ping; Cai, Jia-Liang; Xing, Xiao-Xia; Wang, Ya-Dong; et al.
Abstract: Immune checkpoint blockade (ICB) therapy is an important treatment option for individuals with cancer, but it has certain limitations. Identifying a better target that can overcome tumor immune escape and stimulate T cell activity is critical. This research aimed to delve into the molecular mechanism underlying the immunoregulatory function of metadherin (MTDH), which is a novel and potential therapeutic target in hepatocellular cancer (HCC). A small interfering RNA library was screened using the luciferase reporter assay and PD-L1 promoter. The Cancer Genome Atlas database and HCC tissues were used to investigate the relationship between MTDH and PD-L1. The association between MTDH and β-catenin/lymphoid enhancer binding factor (LEF-1) was discovered by co-immunoprecipitation. The chromatin immunoprecipitation assay was used to investigate the interaction of MTDH with the PD-L1 promoter when LEF-1 expression was silenced. Locked nucleic acid antisense oligonucleotides (ASOs) were used to inhibit MTDH. We utilized in vitro co-cultures and in vivo syngeneic tumor development experiments to confirm the effectiveness of MTDH ASO combined with PD-1 monoclonal antibody (mAb). MTDH was demonstrated to be a PD-L1 modulator. MTDH increased PD-L1 expression and upregulated PD-L1 transcriptional activity through β-catenin/LEF-1 signaling. More importantly, MTDH ASO improved the anti-PD-1 response and increased cytotoxic T-cell infiltration in PD-1 mAb-treated malignancies. MTDH effectively predicts the therapeutic efficacy of ICB therapy. Our results imply that combining MTDH ASO with PD-1 mAb could be a promising therapeutic strategy for HCC. In addition, MTDH is a potential novel biomarker for predicting the effectiveness of immune checkpoint inhibitor treatment. Highlights: Identify MTDH as a potential PD-L1 modulator in HCC. CD8 + T cells were negatively correlated with MTDH in HCC. Pharmacologic inhibition of MTDH led to intense infiltration of CD8 + T cells and sensitized tumors to anti-PD-1 therapy. MTDH may be used to assess anti-PD-1 therapy efficacy. Combination of MTDH ASO and anti-PD-1 provides therapeutic benefit.